Strengthening Financial Sustainability of SMEs Through Government Support: Evidence from the Border Region of Kuningan - Hamzah, Amir; Rahmawati, Teti (Jurnal Cendekia Keuangan, 2025)
Introduction/Main Objectives: This study examines how government support moderates the effects of financial planning, financial record-keeping systems, and capital accessibility on the financial sustainability of Small and Medium Enterprises (SMEs) in the border regions of Kuningan Regency. These SMEs often face limited infrastructure and institutional access, making their financial resilience a critical issue. Background Problems: The research addresses the problem of limited financial sustainability among border-area SMEs by exploring the influence of internal financial practices and external institutional support. Novelty: While prior studies have examined SME financial performance, this research uniquely applies Institutional Theory to analyze how government support—as an institutional factor—affects the relationship between internal financial management and sustainability in border areas. Research Methods: A quantitative approach involving 114 SMEs from Kuningan’s border districts was used. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to assess direct and moderating effects. Finding/Results: Financial planning, record-keeping, and access to capital significantly influence financial sustainability. Government support also positively moderates the link between financial record-keeping and sustainability, but does not consistently moderate other relationships. Conclusion: Financial sustainability in border SMEs is strongly influenced by internal financial practices and selectively supported by government intervention, emphasizing the need for more targeted policies. Research Limitation/Implications: The study is context-specific to Kuningan’s border areas, but it highlights the importance of strengthening financial capabilities and responsive institutional support to improve SME sustainability in similar peripheral regions.